Virilidade, misoginia e violência em a demanda do santo graal e nas crônicas de Fernão Lopes - FERREIRA, Claudienne da Cruz (2021)
This dissertation is dedicated to analyzing gender relations in the medieval period through the aspect of female violence in A Demanda do Santo Graal and in the Chronicles of D. Pedro, D. Fernando and D. João, by Fernão Lopes. Therefore, it was decided to analyze the discourse in the novelist source and the sociological analysis of the chronicles of Fernão Lopes. Violence can be used to fight the enemy, to apply secular or clerical justice, while ideological flag of distinction in relation to others, as well as evidence of the use of virile aggression to control and dominate the female body. In the same way, it is verified in women's counter-hegemonic strategies to overcome misogyny and violence suffered by them. Finally, we conclude that virility and misogyny are mechanisms that contribute to foment violence in its various forms, from the ideological construction that legitimizes intra-personal or interpersonal violence in relationships in society.